Highly mesoporous activated carbon synthesized by pyrolysis of waste polyester textiles and MgCl2: Physiochemical characteristics and pore-forming mechanism. (10th August 2018) - Xu, Zhihua; Yuan, Zhihang; Zhang, Daofang; Chen, Weifang; Huang, Yuanxing; Zhang, Tianqi; Tian, Danqi; Deng, Haixuan; Zhou, Yuwei; Sun, Zhenhua
Abstract: Activation-pyrolysis of textile wastes was considered a sustainable technique to fabricate activated carbon. Highly mesoporous activated carbon was prepared from waste polyester textiles by employing MgCl2 as the activation and template agents. The influences of different preparation conditions on textual property and crystalline structure of carbon were identified by N2 adsorption-desorption isotherms and X-ray diffraction. The optimum pyrolysis temperature, time and mixing ratio for MgCl2 /waste polyester textiles are 900 °C, 1.5 h and 5:5 with the carbon thus obtained manifested a surface area of 1307 m 2 /g, total pore volume of 3.56 cm 3 /g of which 98% is mesopore. The effect of MgCl2 on the full-cycle pyrolysis pathway of waste polyester textiles was systematically investigated by various characterization methods to explore the pore-forming mechanism of activated carbon. The results demonstrated that MgCl2 was capable of catalyzing the dehydrogenation, decarboxylic and cross-linking reaction of waste polyester textiles and inhibited the formation of tars during pyrolysis process, indicating that the addition of MgCl2 was conducive to the formation of carbonaceous materials and open pores. Meanwhile, acted as the template, MgO particles derived from the decomposition of MgCl2 could develop massive homogeneous mesopores in the carbon matrix.